2017
DOI: 10.3390/f8120496
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Traditional Ecological Knowledge and Practices to Forest Management: The Case of Northeast Asia

Abstract: This study aims to introduce the potential applicability of traditional ecological knowledge and community forestry in Northeast Asia, including China, Japan, and South Korea. In ancient Northeast Asia, forest policies and practices were based on Fengshui (an old Chinese concept regarding the flow of vital forces), with which forests were managed under community forestry. However, these traditional systems diminished in the twentieth century owing to the decline of traditional livelihood systems and extreme de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
(132 reference statements)
0
6
0
Order By: Relevance
“…The importance of local access to forest resources to improve welfare has been observed in South Korea (Yeo-Chang 2009). Furthermore, cases from northeast Asia show that TK plays an important role in changing forest management practices in the face of socio-economic change, integrating better into the broader forest management system (Kim et al 2017). Lastly, a case from Zimbabwe found that the role of TK in the conservation of forest and wildlife resources depends largely on social and religious values (Mavhura and Mushure 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of local access to forest resources to improve welfare has been observed in South Korea (Yeo-Chang 2009). Furthermore, cases from northeast Asia show that TK plays an important role in changing forest management practices in the face of socio-economic change, integrating better into the broader forest management system (Kim et al 2017). Lastly, a case from Zimbabwe found that the role of TK in the conservation of forest and wildlife resources depends largely on social and religious values (Mavhura and Mushure 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Most indigenous natural resource management system needs little or no external input, is flexible and evolves with time for which an in-built mechanism in the form of traditional institutions is in place. The TEK of all ethnic communities in traditional forest management system may serve as valuable data for developing conservation strategies (Kim et al 2017). It is mistaken to view forest management practice only in the term of silvicultural approach.…”
Section: Discussion and Concluding Remarkmentioning
confidence: 99%
“…This sustainable forest gardens are owned by families and passed down from one generation to the next while others are managed on a communal basis . This concept of sustainable utilization and management of shared resources is similar to the Village Community Forests (VCFs) of the indigenous peoples of Bangladesh (Misbahuzzaman and Smith-Hall 2015;Chowdhury et al 2018), the "ala-a system" of Ifugaos in the Philippines (Camacho et al 2012), and the Fengshui forest in China (Kim, Li, and Son 2017;Yuan and Liu 2009). It is estimated that there may be over 140 million forest-dependent people in Cambodia, Indonesia, the Philippines, Thailand, and Vietnam, representing about one-third of the population in these nations.…”
Section: Natural Resources Management and Conservationmentioning
confidence: 94%